2020
DOI: 10.1021/acs.joc.9b03061
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Mechanisms of the Banert Cascade with Propargyl Azides

Abstract: Triazoles are privileged heterocycles for a variety of applications. The synthesis of 1H-triazoles can be accomplished by the Banert cascade from propargylic azides. Depending on the substrate and conditions, the Banert cascade can proceed by either a sigmatropic or prototropic mechanism. This report describes the first detailed kinetic analysis of the Banert cascade proceeding by both pathways including substituent effects and KIE. The analysis identified the inflection point in the divergent pathways, allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Recently, the Topczewski´s group have carried out a kinetic analysis of the Banert cascade considering both sigmatropic and prototropic pathways for substituted 1-aryl-3-azido-1butynes. 29 These authors demonstrated that, unlike the sigmatropic reaction, the rate of the prototropic reaction is notably influenced by the aryl substituent. Interestingly, an inflection point was pinpointed in the divergent pathways, which could be useful to predict which Banert product is favoured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Topczewski´s group have carried out a kinetic analysis of the Banert cascade considering both sigmatropic and prototropic pathways for substituted 1-aryl-3-azido-1butynes. 29 These authors demonstrated that, unlike the sigmatropic reaction, the rate of the prototropic reaction is notably influenced by the aryl substituent. Interestingly, an inflection point was pinpointed in the divergent pathways, which could be useful to predict which Banert product is favoured.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, a DFT study of both pathways of the Banert cascade from several propargylic azides, was performed in order to gain a better understanding on the divergent mechanism and rationalize the experimental results. 29 For the prototropic pathway, the methoxide ion was taken as nucleophile. In addition, we have performed a quantum theory of atoms in molecules (QTAIM) and natural bond orbital (NBO) analysis to gain a deeper insight into factor controlling the reactions and to locate some indicator that allow predicting the course of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Forming N H-triazoles by CuAAC or RuAAC has been problematic from the standpoint of reactivity and safety. Thus, we focused on the Banert cascade of propargylic azides (Figure b). This process commences by either a sigmatropic or prototropic rearrangement, resulting in an allenyl azide. , The allenyl azide undergoes electrocyclization to form a triazafulvene . The triazafulvene will polymerize or can be intercepted by exogenous nucleophiles, including alcohols, water, amines, thiols, or azide anion. ,,, We were surprised by a lack of well documented reports utilizing carbon nucleophiles to terminate the Banert cascade. , Presented herein are silver mediated conditions enabling the construction of carbon–carbon bonds α to the newly formed N H-triazole (Figure c).…”
mentioning
confidence: 99%
“…27−29 Thus, we focused on the Banert cascade of propargylic azides (Figure 1b). 30−34 This process commences by either a sigmatropic or prototropic rearrangement, 35 resulting in an allenyl azide. 35,36 The allenyl azide undergoes electrocyclization 37 to form a triazafulvene.…”
mentioning
confidence: 99%
See 1 more Smart Citation